Implementation of STEM-Integrated Problem Based Learning to Improve Students’ Problem Solving Skills in Liquid Pressure - Ramadhani, Firda Amelia; Nurita, Tutut (Jurnal Pendidikan MIPA, 2023)
This research aims to describe the skills of students through the application of STEM-integrated Problem Based Learning on liquid pressure. The subjects of this study were 30 public junior high school students in Surabaya. The type of research was quantitative research. The research design is a quasi-experimental. The research instrument used was a problem-solving skills sheet with indicators: making plans, implementing plans and reviewing results. The data analysis technique used consists of: 1) prerequisite test; 2) Independent t test; and 3) n-gain. The results of the recapitulation of the n-gain category can be seen that 28 students got high selection and 2 students got medium selection. Based on the results obtained, it shows that the STEM-integrated Problem Based Learning has an effect on students' problem-solving skills.Keywords: problem solving skills, problem based learning, STEM.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp349-358